Acute Abdomen caused by Perforated Jejunal Diverticulitis - Raj, Praveena Prithvi; Ang, Chin Wee; Lim, Hiong Chin; Wong, Michael Pak-Kai (IIUM Medical Journal Malaysia, 2021)
Jejunal diverticulum accounts for only 25% of small bowel diverticula, and approximately 7% of these will present as complicated jejunal diverticulitis or perforation. Here, we described a case of jejunal diverticular perforation presented as acute abdominal peritonitis. The computed tomography of the abdomen suggested small bowel perforation and therefore, emergency surgical exploration was performed. Intraoperatively, multiple jejunal diverticulae were found with one forming a localised diverticular abscess. Segmental resection of the diseased segment with primary anastomosis was performed. The patient made an uneventful post-operative recovery. Although complicated jejunal diverticulitis is rare, emergency surgery is often warranted if perforation occurs. Computed tomography is valuable in the diagnosis and preoperative planning especially in an emergency surgical conundrum when there is equivocal clinical peritonitis or perforation.